1988
DOI: 10.1016/0014-5793(88)80884-6
|View full text |Cite
|
Sign up to set email alerts
|

Starvation or diabetes decreases the content but not the mRNA of 6‐phosphofructo‐2‐kinase in rat liver

Abstract: In rat liver, the activity of 6-phosphofructo-2-kinase (PFK-2) decreases upon starvation and in diabetes. Cyclic AMPdependent phosphorylation of the enzyme is not sufficient to account for this decrease. PFK-2 content was therefore measured by immunotitration and relative PFK-2 mRNA levels were determined by hybridization with cDNA probes. The data are compatible with a posttranscriptional mechanism of regulation that involves decreased translational efficiency of PFK-2 mRNA.and (or) increased turnover of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…Glucocorticoids stimulate L-type mRNA PFK-2 transcription in rat liver, 8,39,45 whereas glucagon inhibits transcription and destabilizes the L-mRNA. 46 In starved or diabetic rats, refeeding or insulin treatment increases, 17,47,48 whereas starvation causes a decrease in the PFK-2 mRNA levels, both in lean and obese rats. The effects of insulin on L-promoter, depend on the hormonal context.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids stimulate L-type mRNA PFK-2 transcription in rat liver, 8,39,45 whereas glucagon inhibits transcription and destabilizes the L-mRNA. 46 In starved or diabetic rats, refeeding or insulin treatment increases, 17,47,48 whereas starvation causes a decrease in the PFK-2 mRNA levels, both in lean and obese rats. The effects of insulin on L-promoter, depend on the hormonal context.…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon inhibits transcription from the L promoter and destabilizes the L mRNA in vivo [51]. In fasted or diabetic rats, refeeding or insulin treatment increases PFK-2/FBPase-2 mRNA concentration in liver after 24-48 h [52][53][54]. Cifuentes et al [49] and Espinet et al [46] [40] identified in liver chromatin five DNAase I-hypersensitive sites, two of which could correspond to other regulatory regions of gene A.…”
Section: Gene Organizationmentioning
confidence: 99%
“…Expression of the L, but not the M, isozyme of PFK-2/FBPase-2 is controlled by diet and insulin (6,7).…”
mentioning
confidence: 99%